Low-profile reconfigurable UWB fractal antenna enhanced by parasitic elements for wireless applications - Al Gburi, Ahmed Jamal Abdullah; Marzouk, Mohamed; Nejdi, Ibrahime Hassan; Rhazi, Youssef; Saih, Mohamed; Abdul Nasir, Jamal; Daher, Abdulrahman; Hussien, Mousa I.; Zakaria, Zahriladha (Electromagnetics Academy, 2025)
This paper presents an enhanced design of a reconfigurable fractal ultra-wideband (UWB) antenna, improved through the inclusion of parasitic elements. The antenna incorporates two plus-shaped parasitic elements and a hexagonal radiating patch, while maintaining compact dimensions of 30 mm × 22 mm × 1.6 mm on an FR4 substrate. A partial ground plane with an integrated rectangular slot is etched on the backside of the resonator. The antenna was designed using HFSS, fabricated, and experimentally validated. The measured results show good agreement with the simulations. It operates over a frequency range of 4 to 10.57 GHz, with resonant frequencies at 4.7, 7.92, and 10 GHz. The design achieves a gain between 2.76 and 5.83 dB and maintains high radiation efficiency ranging from 82% to 95%. To further enhance performance, two strategically placed HPND-4005 PIN diodes are incorporated, allowing tunable resonance characteristics by altering current distribution under various switch configurations. As a result, the reconfigurable antenna extends its operational bandwidth from 3 to 14 GHz, making it suitable for a variety of wireless applications such as Wi-Fi, WiMAX, WLAN, and C-, X-, and Ku-band communications. Notably, the design achieves this wideband reconfigurability using only two PIN diodes while maintaining a compact footprint — offering an advantage over previous designs. Its features support seamless integration into compact electronic devices, enabling manufacturers to incorporate multiple antennas with minimal complexity.